2014
DOI: 10.1186/1471-2369-15-146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microalbuminuria and diagnostic value of dipstick proteinuria in outpatients from HIV clinics in Bukavu, the Democratic Republic of Congo

Abstract: BackgroundMicroalbuminuria is a marker of early kidney disease and high cardiovascular risk in various populations, including HIV positive patients. However, the diagnostic value of qualitative (dipstick) proteinuria and the burden of microalbuminuria in HIV positive patients living in sub-Saharan Africa are relatively unclear.MethodsIn a cross-sectional study, 235 HIV- positive outpatients were screened for proteinuria in 3 HIV-clinics in Bukavu. A spot urine sample from each subject was tested both by a dips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
(25 reference statements)
2
16
1
Order By: Relevance
“…This high prevalence of microalbuminuria highlights the magnitude of early renal dysfunction in HIV-infected patients before ART initiation. This was different from most of the studies conducted in recent times [5][6][7][8][9][10][11][12][13].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This high prevalence of microalbuminuria highlights the magnitude of early renal dysfunction in HIV-infected patients before ART initiation. This was different from most of the studies conducted in recent times [5][6][7][8][9][10][11][12][13].…”
Section: Discussioncontrasting
confidence: 80%
“…However, they used test strips that have been found to have poorer validity and reliability [15] than spectrophotometry we used in our study and their patients had relatively lower mean CD4 + count compared to our study (200 versus 466 cells/µL). Notably, there were two studies in adults that demonstrated lower prevalence 8.9% [11]and 14% [6] in Democratic Republic of Congo (DRC) and USA respectively. Overall, the differences in screening methodologies and the clinical characteristics of study participants probably explain the varied results among studies in relation to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the prevalence of positivity for microalbuminuria in the urinary test was high, from 61 to 49.7%, and we managed to show a decreasing trend in the levels of microalbuminuria observed during the 48-weeks of observation, probably because of the criterion used for the diagnosis of microalbuminuria that allows to highlight even early alterations. The prevalence of microalbuminuria in HIV+ population was estimated to be ranging from 50 to 58% [ 9 , 20 , 21 ]. In another cohort of HIV+ patients, these values were three to five times lower than in this study and compared to the general population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change in the recommendation was because, among many other reasons, urine dipstick testing for proteinuria was shown to be less sensitive than quantitative proteinuria [ 19 ]. Similarly, a subsequent study revealed that dipstick analysis has limited diagnostic value to detect albuminuria [ 20 ]. However, both studies had relatively small sample sizes and high prevalence of proteinuria that could lead to a selection bias, which might diminish the proportion of patients with low level albuminuria or proteinuria.…”
mentioning
confidence: 99%